2018
DOI: 10.1002/mc.22830
|View full text |Cite
|
Sign up to set email alerts
|

A novel tricarbonylmethane agent (CMC2.24) reduces human pancreatic tumor growth in mice by targeting Ras

Abstract: Pancreatic Cancer (PC) is a deadly disease in need of new therapeutic options. We recently developed a novel tricarbonylmethane agent (CMC2.24) as a therapeutic agent for PC, and evaluated its efficacy in preclinical models of PC. CMC2.24 inhibited the growth of various human PC cell lines in a concentration and time-dependent manner. Normal human pancreatic epithelial cells were resistant to CMC2.24, indicating selectivity. CMC2.24 reduced the growth of subcutaneous and orthotopic PC xenografts in mice by up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Whole cell protein lysates were prepared, and electrophoresis and electroblotting were performed as previously described [31]. Membranes were probed overnight with the following primary antibodies (1:1000 dilution) from Cell Signaling Technology (Danvers, MA, USA): PFKP (Cat #8164), PKM2 (Cat #4053), HK2 (Cat #2867), LDHA (Cat #3582), phospho-Chk1 (Ser345) (Cat #2348), phospho-p53 (Ser15) (Cat #9286), p53 (Cat #2527), p21 Waf1/Cip1 (Cat #2947), cdc2 (Cat #28439), Cyclin B1 (Cat #12231), Caspase-3 (Cat #14220), Caspase-7 (Cat #12827), Caspase-9 (Cat #9508), and PARP (Cat #9542).…”
Section: Methodsmentioning
confidence: 99%
“…Whole cell protein lysates were prepared, and electrophoresis and electroblotting were performed as previously described [31]. Membranes were probed overnight with the following primary antibodies (1:1000 dilution) from Cell Signaling Technology (Danvers, MA, USA): PFKP (Cat #8164), PKM2 (Cat #4053), HK2 (Cat #2867), LDHA (Cat #3582), phospho-Chk1 (Ser345) (Cat #2348), phospho-p53 (Ser15) (Cat #9286), p53 (Cat #2527), p21 Waf1/Cip1 (Cat #2947), cdc2 (Cat #28439), Cyclin B1 (Cat #12231), Caspase-3 (Cat #14220), Caspase-7 (Cat #12827), Caspase-9 (Cat #9508), and PARP (Cat #9542).…”
Section: Methodsmentioning
confidence: 99%
“…Of particular interest, Mackenzie's group at Stony Brook's Cancer Center recently demonstrated that chemically modified curcumin-2.24 induced apoptosis in pancreatic cancer cells and reduced pancreatic tumor growth by inhibiting active Ras and signal transducer and activator of transcription-3 phosphorylation. 135 Moreover, even at high (1000 mg/kg) oral doses, the animals treated with chemically modified curcumin-2.24 showed no evidence of toxicity (Heta Bhatt et al, unpublished data). As reviewed recently by Mendes et al, 136 the subset of sirtuins that are of particular relevance to periodontal disease include 7 proteins (sirtuins 1-7) with different subcellular locations, mitochondria, cytoplasm, or nucleus.…”
Section: Cancermentioning
confidence: 99%
“…Wright et al reported that in a mouse model of medulloblastoma, treatment with chemically modified curcumin‐2.24 combined with a curcumin‐phosphatidyl choline (to improve bioavailability) showed therapeutic efficacy in controlling tumor growth. Of particular interest, Mackenzie's group at Stony Brook's Cancer Center recently demonstrated that chemically modified curcumin‐2.24 induced apoptosis in pancreatic cancer cells and reduced pancreatic tumor growth by inhibiting active Ras and signal transducer and activator of transcription‐3 phosphorylation . Moreover, even at high (1000 mg/kg) oral doses, the animals treated with chemically modified curcumin‐2.24 showed no evidence of toxicity (Heta Bhatt et al, unpublished data).…”
Section: Future Host‐modulation Agents: the Chemically Modified Curcuminsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has reported on CMC2.24, a triketonic N -phenylaminocarbonyl derivative of bis-demethoxycurcumin, which exhibits enhanced stability and solubility compared to curcumin and has emerged as a ‘lead compound’ for several pharmacological applications such as treatment of anthrax by inhibition of the metalloprotease, lethal factor [ 21 ], treatment of cancers of the pancreas [ 22 ] and prostate [ 23 ], normalizing wound healing in diabetic rats [ 24 ], reduction in severity of periodontitis and inhibition of alveolar bone resorption associated with the disease in a rat model [ 25 , 26 ]. In addition, CMC2.24 has shown superior anti-inflammatory activity compared to the parent compound curcumin, in inhibiting periodontitis-induced bone resorption in rats via multiple mechanisms [ 27 ], and most recently, for the treatment of natural periodontitis in beagle dogs [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%